The Wiley Blackwell handbook of social anxiety disorder - Weeks, Justin W. (Chichester, West Sussex : Malden, MA : John Wiley & Sons, Ltd., 2014)
Featuring leading international authors working in clinical psychology and psychiatry, this handbook offer the most in-depth coverage of social anxiety disorder, including personality factors in SAD, and multicultural issues in the diagnosis, case conceptualization, and treatment of SAD. A multi-contributed, internationally diverse handbook covering all major elements of social anxiety disorder, offering an invaluable teaching toolThis unique text contributes significantly to the field by summarizing the current state of research in the area and outlining future directionsProvides a comprehen
Conclusions and Future DirectionsReferences; 4 The Social Neuroscience of Social Anxiety Disorder; Introduction; The Scope of this Essay; Part 1: Current Research on Social Neuroscience of SAD; Brain Imaging of Socioemotional Processing in SAD; Physiological and Behavioral Data; Summary; Part 2: Social Neuroscientific Directions for Future Research in SAD; Genetics of SAD; Immune Function in SAD; Social Isolation in Social Anxiety; Self-Reference, Self-Reappraisal, and Social Others in SAD; Limited Scope of Currently Used Social Stimuli in SAD Research.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Social phobia -- Handbooks, manuals, etc; Anxiety -- Handbooks, manuals, etc; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Anxiety; Social phobia; Anxiety -- Handbooks, manuals, etc; Social phobia -- Handbooks, manuals, etc; Anxiety Disorders -- therapy; Anxiety Disorders; Social Adjustment; Electronic books; Handbooks and manuals; Electronic books